2019
DOI: 10.1038/s41598-019-42401-9
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of donor and recipient CD8+ tissue-resident memory T cells in transplant nephrectomies

Abstract: Tissue-resident memory T (T RM ) cells are characterized by their surface expression of CD69 and can be subdivided in CD103+ and CD103− T RM cells. The origin and functional characteristics of T RM cells in the renal allograft are largely unknown. To determine these features we studied T RM cells in transplant nephrectomies. T RM cells with a CD103+ and CD103− phenotype were present in all samples… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
45
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(49 citation statements)
references
References 43 publications
4
45
0
Order By: Relevance
“…As expected, the genes downregulated in CD69 + T cells were either not detected or were found at low levels in both clusters ( Figures S2 D and S2E). However, several T RM cell-associated genes upregulated in CD69 + T cells were differentially expressed between the two clusters, with population 1 expressing more ITGAE and ITGA1 (in agreement with work on renal T RM cells [ de Leur et al., 2019 ]), and population 2 expressing more CRTAM ( Figures 2 D, 2F, and S2 F). T cell receptor (TCR) repertoire analysis revealed the presence of shared clonotypes between the two T RM clusters ( Figure S2 G).…”
Section: Resultssupporting
confidence: 86%
“…As expected, the genes downregulated in CD69 + T cells were either not detected or were found at low levels in both clusters ( Figures S2 D and S2E). However, several T RM cell-associated genes upregulated in CD69 + T cells were differentially expressed between the two clusters, with population 1 expressing more ITGAE and ITGA1 (in agreement with work on renal T RM cells [ de Leur et al., 2019 ]), and population 2 expressing more CRTAM ( Figures 2 D, 2F, and S2 F). T cell receptor (TCR) repertoire analysis revealed the presence of shared clonotypes between the two T RM clusters ( Figure S2 G).…”
Section: Resultssupporting
confidence: 86%
“…A previous study reported that donor T cells were associated with the transplant outcome of lungs 33 , and therefore the presence or abundance of donor T cells may be related to kidney transplant outcome. A previous study identified the presence of donor-derived CD8 + T RM cells was associated with graft failure in the first month after transplantation 34 . Additionally, an abundance of T cells may affect the surveillance of kidney cancers because this cancer type is typically immunogenic and T cell-dependent 35 .…”
Section: Discussionmentioning
confidence: 94%
“…Patients experiencing cardiac allograft rejection show distinct changes in CD4 + and CD8 + T‐cell subsets in peripheral blood samples . In the process of allograft rejection, donor‐derived tissue‐resident CD8 + T‐cells become gradually replaced by alloreactive, recipient‐derived CD8 + T‐cells with strong effector abilities and high levels of intracellular granzyme B . Through staining of CD3 + T‐cells in the rejected hearts, we demonstrated that graft rejection in our model was clearly accompanied by T‐cell infiltration.…”
Section: Discussionmentioning
confidence: 67%
“…The in vitro model, where MSCs, but not HI‐MSCs suppressed CD3 + T‐cell proliferation provided mechanistic insights into the differential effects of MSCs and HI‐MSCs in T‐cell‐mediated allograft rejection. We revealed that only MSCs are able to suppress the granzyme B‐mediated cytotoxic CD8 + T‐cell response, which is known as one of the principal mediators of acute allograft rejection . MSCs have been shown to suppress T‐cell proliferation and shift the effector functions of T‐cells toward regulatory functions, mainly through the expression of immunomodulatory molecules such as IDO, and secretion of prostaglandin‐E2 (PGE2), nitric oxide, and TGF‐β .…”
Section: Discussionmentioning
confidence: 99%